Management of Horticultural Extension Services In Rainfed Areas - G.R. Desai; P.L. Manohari (Journal of Agricultural Extension Management, 2025)
India has varied agro climatic conditions and natural resources to grow a large spectrum of horticultural crops like fruits, vegetables, flowers, tubers and plantations like cashew, areca nut, cardamom, rubber, coconut etc. Though the area under horticulture is only 8.5 percent, its contribution to the GDP in agriculture is to the tune of 28.5 per cent which is significant